2013
DOI: 10.1016/j.laa.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Fractional perfect b-matching polytopes I: General theory

Abstract: The fractional perfect b-matching polytope of an undirected graph G is the polytope of all assignments of nonnegative real numbers to the edges of G such that the sum of the numbers over all edges incident to any vertex v is a prescribed nonnegative number b v . General theorems which provide conditions for nonemptiness, give a formula for the dimension, and characterize the vertices, edges and face lattices of such polytopes are obtained. Many of these results are expressed in terms of certain spanning subgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Proof of claim. A proof of the above lemma can be derived from the results given in [4]. We report the details for completeness.…”
Section: Lower Boundmentioning
confidence: 98%
See 1 more Smart Citation
“…Proof of claim. A proof of the above lemma can be derived from the results given in [4]. We report the details for completeness.…”
Section: Lower Boundmentioning
confidence: 98%
“…Using this result, it is easy to derive adjacency properties for the vertices of P F M . We here explicitly state a lemma that follows from Theorem 25 in [4]. This lemma gives some sufficient conditions for two vertices of P F M to be adjacent.…”
Section: Preliminariesmentioning
confidence: 99%
“…The adjacency of these fractional polytopes is given in Theorem 25 of [2]. In the following we will only use the fact that the graph of M(G) and PM(G) are, respectively, a subgraph of FM(G) and FPM(G).…”
Section: Monotone and Simplex Paths On Cubes And Zonotopesmentioning
confidence: 99%
“…Let us denote by C(P FMAT (G)) the set of circuits of P FMAT (G) with co-prime integer components. [4,27]), so it remains to be shown that all circuits belong to one of these sets. Let B denote the constraint matrix corresponding to the constraints (2).…”
Section: Key Tool: the Circuits Of The Fractional Matching Polytopementioning
confidence: 99%
“…We first characterize the circuits of the more general fractional matching polytope, i.e., the polytope given by the standard LP-relaxation for the matching problem on general graphs, in Section 3.1. This builds on the known graphical characterization of adjacency given in [27,4]. Then, we construct a reduction from the NP-hard Hamiltonian path problem in Section 3.2 1 .…”
Section: Introductionmentioning
confidence: 99%